The Influence of Family Environment and Learning Motivation on Learning Outcomes in Economics Subjects - Rosiana Rahmawati; Muniru Azuug; Amiruddin Ismail (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The aim of this research is to determine whether there is an influence of family environmental variables and learning motivation simultaneously on learning outcomes in economics subjects. To determine whether or not there is a partial influence of family environmental variables on learning outcomes in economics subjects. And to find out whether there is a partial influence of learning motivation variables on learning outcomes in economics subjects. Methodology: This type of research is descriptive quantitative with survey methods. The population in this study was class X high school students, totaling 450 students with a sample size of 82 respondents. Sampling used the proportionate random sampling technique by lottery. The research data collection technique uses a questionnaire. Data validity was obtained through the results of a tryout conducted on 30 respondents. The data analysis technique used is multiple linear regression analysis technique. Main Findings: Based on this research, (1) There is a significant influence between family environment variables and learning motivation simultaneously on students' economics learning outcomes; (2) Family environment variables partially have a significant influence on students' economics learning outcomes; (3) Partial learning motivation variables also have a significant influence on students' learning outcomes in economics subjects; (4) The coefficient of determination (R square) of 0.455 or 45.5% indicates that the family environment and learning motivation together influence 45.5% of student learning outcomes in economics subjects. Novelty/Originality of this study: This research investigates the influence of family environmental variables and learning motivation simultaneously on learning outcomes in economics subjects. Previous studies may not have combined these two variables simultaneously in the same context. This research also partially tests the influence of family environmental variables on learning outcomes in economics subjects.